2001
DOI: 10.1590/s0100-879x2001000400003
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of calcium in pain and antinociception

Abstract: Calcium ions are widely recognized to play a fundamental role in the regulation of several biological processes. Transient changes in cytoplasmic calcium ion concentration represent a key step for neurotransmitter release and the modulation of cell membrane excitability. Evidence has accumulated for the involvement of calcium ions also in nociception and antinociception, including the analgesic effects produced by opioids. The combination of opioids with drugs able to interfere with calcium ion functions in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 46 publications
2
35
0
5
Order By: Relevance
“…[16,25,32,34]. Furthermore, Ca 2+ chelators or antagonists of L-, N-and P-type Ca 2+ channels, potentated -opioid receptor-mediated antinociception [25,27]. Conversely, the antinociception produced by selective ␦-opioid receptor agonists was potentated by agents that increase intracellular Ca 2+ whereas it was reduced by i.c.v.…”
Section: Introductionmentioning
confidence: 99%
“…[16,25,32,34]. Furthermore, Ca 2+ chelators or antagonists of L-, N-and P-type Ca 2+ channels, potentated -opioid receptor-mediated antinociception [25,27]. Conversely, the antinociception produced by selective ␦-opioid receptor agonists was potentated by agents that increase intracellular Ca 2+ whereas it was reduced by i.c.v.…”
Section: Introductionmentioning
confidence: 99%
“…These drugs act as antagonists on N- (15,16) and P/ Q-type (17) VOCC. A marked similarity between the effects of aminoglycoside antibiotics and magnesium ions, as well as a prompt antagonism of their effects when the extracellular Ca 2+ concentration is increased, have been demonstrated earlier in neuromuscular transmission (for a review, see 11), and confirmed in models of artificial membranes, in rodent cardiac and smooth muscles, and isolated mast cells (for a review, see 18). Antinociception following gentamicin has been demonstrated in rodent models of phasic or persistent pain (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 76%
“…Ca 2+ influx occurs mainly through L-, N-, P/Q-, and T-type voltage-operated calcium channels (VOCC) (for a review, see 1,10). Antagonists of L-type VOCC potentiate opiate analgesia in rodents, but this effect depends on the route of administration and the algesimetric test used (for a review, see 11). Mibefredil (12), a selective T-type VOCC antagonist, does not alter the response of mice in the tail-flick test.…”
Section: Introductionmentioning
confidence: 99%
“…The VGCCs most extensively studied in nociception are the N-, P/Q-and T-type Ca 2+ channels [45][46][47]. It is well established that an increase in intracellular Ca 2+ has an important role in neurotransmitter release, cell membrane excitability, activation of intracellular proteins, and reduction of the pain threshold [48][49][50]. The concentration of intracellular Ca 2+ is regulated by several mechanisms; one such mechanism is the influx of Ca 2+ via VGCCs through the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%